Clinical Observation of the Efficacy of Endoscopic Retrograde Cholangiopancreatography on Elder Choledocholithiasis and Its Effects on the Levels of TNF-α, IL-1, and IL-6 - Shen,Yun-zhi (2018)
SUMMARY OBJECTIVE: We conducted this study to investigate the clinical efficacy of endoscopic retrograde cholangiopancreatography (ERCP) on elder choledocholithiasis and its effects on the levels of TNF-α, IL-1, and IL-6. METHODS: Elder patients with choledocholithiasis were enrolled in this study, and according to the surgical methods, they were divided into the ERCP group and the surgical group. After treatment, we compared the efficacy of these two methods on patients, inflammatory responses indicated by the levels of TNF-α, IL-1, and IL-6, and the complications. RESULTS: No statistical significance was identified in the difference of the success rate in removal between the two groups (98% vs. 94%), but indicators of the ERCP group, including the surgical duration (28.5±12.8) min, remission duration of abdominal pain (1.2±0.2) d, recession time of jaundice (2.0±0.3) d, postoperative bedridden time (1.4±0.2) d, treatment time of the anti-infection (1.5±0.2) d, length of stay in hospital (6.5±0.3) d, levels of TNF-α (2.1±0.2) μg/L, IL-1 (6.3±0.8) μg/L, IL-6 (2.8±0.3) μg/L, and the incidence rate of complications (1.8%), were all significantly lower than those in the surgical group (p<0.05). CONCLUSION: In the treatment of choledocholithiasis, ERCP is excellent in controlling the trauma, accelerating the recovery duration, reducing the occurrence of complications and ameliorating the inflammatory responses. Thus, it is an ideal choice for choledocholithiasis.